IMPLEMENTASI PROGRAM PERLINDUNGAN KESEHATAN DAN KESELAMATAN KERJA (K3) BAGI PEKERJA OUTSOURCING DI PT. HKM RANDUAGUNG, SINGOSARI - Rima Audiya; Agus Prianto (Journal Publicuho, 2025)
This study aims to evaluate the implementation of the Occupational Health and Safety (OHS) protection program for outsourced workers at PT. Huwana Karya Makmur Randuagung Singosari. The approach used is descriptive qualitative with the George C. Edward III policy implementation model, which includes four main variables: communication, resources, implementer disposition, and bureaucratic structure. The results of the study indicate that the implementation of the OHS policy has not been running optimally, especially for outsourced workers who experience information inequality, limited access to occupational safety facilities, and a lack of equitable supervision. The dualistic organisational structure between permanent and outsourced workers also weakens the effectiveness of policy implementation. Therefore, improved communication, fair resource allocation, strengthening implementer commitment, and reform of the bureaucratic structure are needed so that the OHS policy can be implemented more inclusively and equitably. These findings provide an important contribution to strengthening the protection of outsourced workers in the industrial sector.